Optimization of mercury removal using palm oil fuel ash - Nor Akmalina, Mustazar (2017)
The palm oil fuel ashes (POFA) were used as biosorbent for the removal of heavy metals ions from wastewater. From the preliminary experimental results, it shows that the POFA had good adsorption capability for Hg (II) ions. This study aims to employ low-cost biosorbent such as activated palm oil fuel ash to remove mercury (II) from wastewater. Initially, 5factors were screened using 25-1 factorial analysis. Factors that gave the significant effect which are contact time and agitation speed had a maximum point which is likely to be the optimum point and possible for the optimization process. The effect of two biosorption variables (contact time and agitation speed) were investigated using central composite design (CCD) which is a subset of response surface methodology (RSM). Quadratic model was developed for Hg (II) percentage removals. A 22 factorial central composite design was used to get the mutual interaction between variables. The optimum adsorption conditions were obtained at contact time of 5 hr and agitation speed of 150 rpm with desirability of 0.95. At these optimum points, the mercury removal efficiency was calculated as 98.93 % in batch mode. Based on the predicted and experimental results presented, the experimental values were in good agreement with the predicted values proposed by the model with an error less than 10 % and proved to be an adequate model. The results indicated that POFA has the potential to be used as an adsorbent for the removal of Hg (II) from aqueous environments due to its significant adsorption capacity and naturally abundance at low cost value.